The effects of empagliflozin on hepatic parameters and liver fat content in patients with type 2 diabetes mellitus: a systematic review and meta-analysis - Ying, Lim Kar (2024)
Background: Type 2 Diabetes Mellitus (T2DM) often coexists with hepatic complications, including Non-Alcoholic Fatty Liver Disease (NAFLD), posing significant challenges in treatment strategies. Empagliflozin, a Sodium-Glucose Co-Transporter 2 (SGLT2) inhibitor, has garnered attention for managing T2DM and improving hepatic parameters. However, existing evidence on its impact on hepatic outcomes in T2DM patients remains inconclusive, necessitating further investigation. This meta-analysis aims to comprehensively evaluate the effect of empagliflozin on hepatic parameters and liver fat percentage (LFP) in individuals with T2DM. Methods: Following PRISMA guidelines, a thorough search spanned databases such as PubMed, Scopus, Web of Science, Google Scholar, Cochrane Library, and ClinicalTrials.gov from inception to January 2023. The inclusion criteria includes patients with T2DM, interventions of empagliflozin versus placebo or standard treatment, and study with randomized controlled trial design. Exclusion criteria encompass book chapters, narrative reviews, and study protocols. Quality assessment followed the Revised Cochrane risk-of-bias tool for randomized trials (RoB 2). The effect size estimate was derived from post-treatment values of hepatic parameters (alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transpeptidase (GGT)) and LFP, comparing empagliflozin-treated groups with other Background: Type 2 Diabetes Mellitus (T2DM) often coexists with hepatic complications, including Non-Alcoholic Fatty Liver Disease (NAFLD), posing significant challenges in treatment strategies. Empagliflozin, a Sodium-Glucose Co-Transporter 2 (SGLT2) inhibitor, has garnered attention for managing T2DM and improving hepatic parameters. However, existing evidence on its impact on hepatic outcomes in T2DM patients remains inconclusive, necessitating further investigation. This meta-analysis aims to comprehensively evaluate the effect of empagliflozin on hepatic parameters and liver fat percentage (LFP) in individuals with T2DM. Methods: Following PRISMA guidelines, a thorough search spanned databases such as PubMed, Scopus, Web of Science, Google Scholar, Cochrane Library, and ClinicalTrials.gov from inception to January 2023. The inclusion criteria includes patients with T2DM, interventions of empagliflozin versus placebo or standard treatment, and study with randomized controlled trial design. Exclusion criteria encompass book chapters, narrative reviews, and study protocols. Quality assessment followed the Revised Cochrane risk-of-bias tool for randomized trials (RoB 2). The effect size estimate was derived from post-treatment values of hepatic parameters (alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transpeptidase (GGT)) and LFP, comparing empagliflozin-treated groups with other groups. Statistical analysis was performed using R Software version 4.2.3, involving determination of treatment effects, assessment of heterogeneity, and sensitivity analysis. Results: The meta-analysis includes 6 studies, totalling 565 participants, with 7 effect size estimates for ALT. For AST, 6 effect sizes from 5 studies were pooled (458 observations), while GGT analysis included data from 4 studies (353 observations), and LFP analysis involved two studies (202 observations). For ALT level, no significant mean difference (MD) in ALT levels was found between individuals treated with empagliflozin and the control group in the initial analysis (MD = - 5.59; 95% CI [-10.98; 1.46]; p = 0.100). However, substantial heterogeneity (I2 = 85%) indicated considerable variability among studies. Further exploration revealed significant variability (Q = 41.30, p < 0.001) and wide prediction interval (PI) that ranged from -22.80 to 11.62. Upon sensitivity analysis and removal of influential study, heterogeneity dropped from 85.5% to 0.0%, but the MD remained non-significant (MD = - 2.08; 95% CI [- 5.82; 1.65], p = 0.211). In our analysis of AST levels, the initial meta-analysis showed no significant difference in AST levels between empagliflozin-treated individuals and the control group (MD = -5.44; 95% CI [-11.02 – 0.14]; p = 0.054). Despite this, there was substantial heterogeneity (I2 = 82%) among the studies, indicating diverse effects. Further heterogeneity tests confirmed significant variability (Q = 27.77, d.f. = 5, p < 0.001), suggesting underlying factors contributing to differences across studies. The wide prediction interval (-19.49 to 8.61) indicates uncertainty in estimating the true treatment effect. Sensitivity analyses identified one influential study. Removing this study reduced heterogeneity (from 82.0% to 26.8%), but the MD remained non-significant (MD = -2.54; 95% CI [-6.50; 1.42], p = 0.150). Despite efforts to address heterogeneity, statistically significant results were not obtained, indicating a trend but lacking statistical significance for AST levels. In our analysis of GGT levels, the pooled estimate revealed a significant difference in post-treatment GGT levels between individuals treated with empagliflozin and the comparator groups (MD = -10.86; 95% CI [-20.18; -1.53], p = 0.034), with heterogeneity below the threshold of significance (I2 = 31%). PI for GGT level spanned from -29.18 to 7.47. No study was removed as influential for GGT level. The analysis of LFP showed a non-significant mean difference (MD -4.903, 95% CI [-9.869; 0.064], p = 0.0507). Only two studies were included in the analysis for LFP, precluding subsequent analyses for heterogeneity, publication bias, sensitivity analysis, and influential analysis due to the limited sample size. Conclusion: Empagliflozin did not significantly affect ALT and AST levels at 10 mg dosage. Higher dosage (25 mg) may benefit liver parameters. Significant reduction in GGT levels was observed, yet with limited data. No significant impact on LFP was noted. Further research is warranted to explore empagliflozin's efficacy at 25mg dosage for improving hepatic outcomes.